2016
DOI: 10.1515/jpm-2016-0204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the duo of insulin-like growth factor binding protein-1/alpha fetoprotein (Amnioquick duo+®) and traditional clinical assessment for diagnosing premature rupture of fetal membranes

Abstract: The performance matrix of Amnioquick duo+® was superior to that of TCA for diagnosing PROM even in equivocal cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Here, we report the results of the Amnioquick duo+ versus PAMG‐1 test. Results of the cohort evaluated with Amnioquick duo+ versus conventional methods have been published separately …”
Section: Introductionmentioning
confidence: 99%
“…Here, we report the results of the Amnioquick duo+ versus PAMG‐1 test. Results of the cohort evaluated with Amnioquick duo+ versus conventional methods have been published separately …”
Section: Introductionmentioning
confidence: 99%
“…The present study predicted histologically confirmed chorioamnionitis using the Chorioquick test, which was in line with criteria used in previous studies. 4,17,21 Compared to binary tests used in previous studies, the scientific evidence to assume that the semi-quantitative IL-6 marker in Chorioquick would be a good test to diagnose sub-clinical In conclusion, the present study-the first into the Chorioquick test-showed favorable utility for detecting chorioamnionitis in PROM and could be a more reliable, non-invasive rapid tool in a realworld clinical setting, especially for those with some degree of acute chorioamnionitis. To our knowledge, this was the first time that a semi-quantitative bedside test has been used to evaluate IL-6 from cervicovaginal secretions in women with PROM.…”
Section: Discussionmentioning
confidence: 71%
“…The AmnioQuick Duo+ test detects the presence of AFP and IGFBP‐1 in vaginal samples . The vaginal specimen was obtained via a swab stick placed in the posterior fornix for 1 minute.…”
Section: Methodsmentioning
confidence: 99%
“…The AmnioQuick Duo+ test detects the presence of AFP and IGFBP-1 in vaginal samples. 10 The vaginal specimen was obtained via a swab stick placed in the posterior fornix for 1 minute. A buffer tube was used to rinse the swab for 10 seconds; in some cases, the tip of the swab was broken off into the buffer tube and the contents were shaken.…”
Section: Methodsmentioning
confidence: 99%